Analysis of Differences in Student Learning Achievement: A Review of Gender and Majors - Afrinaldi Afrinaldi; M Arif; Yantri Maputra; Sahlan bin Surat (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2022)
The article explains student learning achievement, then looks at differences in student learning achievement in terms of gender and major aspects. This research uses a combined approach through descriptive and inferential quantitative approaches. Data collection using questionnaires and documentation. A total of 438 samples have been studied through random sampling techniques to see differences in learning achievement for male and female students in science and social studies majors. Data were also collected by interviewing 12 students and 3 teachers, the selection of informants referring to social situations, the selection of informants was carried out with a purposeful sample technique. Data analysis using the t-test found that learning achievement was no difference in terms of background majoring in science and social studies, in contrast to gender there were differences in learning achievement between male and female students. Qualitative data analysis obtained by students practicing learning achievements in the form of memorization, understanding, practice, and evaluation. Meanwhile, affective learning achievement through aspects of: receiving, responding, valuing, organizing. Psychomotor academic achievement on aspects of: reflex movements, basic skills, physical skills.